2013
DOI: 10.1177/2040622313478646
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of autoimmune liver disease: current and future therapeutic options

Abstract: Autoimmune liver disease spans three predominant processes, from the interface hepatitis of autoimmune hepatitis to the lymphocytic cholangitis of primary biliary cirrhosis, and finally the obstructive fibrosing sclerotic cholangiopathy of primary sclerosing cholangitis. Although all autoimmune in origin, they differ in their epidemiology, presentation and response to immunosuppressive therapy and bile acid based treatments. With an ongoing better appreciation of disease aetiology and pathogenesis, treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 187 publications
(339 reference statements)
0
38
0
2
Order By: Relevance
“…In type 1 antinuclear antibodies, smooth muscle antibodies and antibodies against soluble liver antigen/liverpancreas are detected, while patients with type 2 typically generate antibodies to liver/kidney microsomal antigen type-1 and liver cytosol antigen type 1. In most cases, AIH is responsive to immunosuppressants, although adverse effects are common and alternative treatments are lacking [79] . Environmental triggers for AIH are largely unknown but may include drug and toxin exposure, as well as hitherto unidentified viral infections [80] .…”
Section: Hla Associations For Immune-mediated Liver Diseases Point Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In type 1 antinuclear antibodies, smooth muscle antibodies and antibodies against soluble liver antigen/liverpancreas are detected, while patients with type 2 typically generate antibodies to liver/kidney microsomal antigen type-1 and liver cytosol antigen type 1. In most cases, AIH is responsive to immunosuppressants, although adverse effects are common and alternative treatments are lacking [79] . Environmental triggers for AIH are largely unknown but may include drug and toxin exposure, as well as hitherto unidentified viral infections [80] .…”
Section: Hla Associations For Immune-mediated Liver Diseases Point Tomentioning
confidence: 99%
“…The initiation of immune reactivity to PDC-E2 is yet to be determined, but environmental factors, such as smoking, infection and xenobiotics may promote the loss of selftolerance by means of "molecular mimicry," wherein the exposure to exogenous antigens triggers autoimmunity to endogenous molecules expressing a similar epitope (mimitope) [83] . Treatment for PBC is largely restricted to ursodeoxycholic acid, which delays liver injury successfully for some patients but shows limited efficacy in a significant number of cases [79] .…”
Section: Hla Associations For Immune-mediated Liver Diseases Point Tomentioning
confidence: 99%
“…The therapy is, however, still useful because it can reduce the activity of the disease. 14,23 Immunosuppressive treatment may be considered in asymptomatic adult patients with mild laboratory and histological changes, but the decision must be individualized and balanced against the possible side effects of the therapy. 7 Patients with minimal or no disease activity or inactive cirrhosis should not be treated, but must continue to be followed closely, i.e., 3-6 months.…”
Section: Therapymentioning
confidence: 99%
“…49,50 Patients with stage I/II PBC achieving an AST and alkaline phosphatase (ALP) less than 1.5×upper limit of normal (ULN) and normal bilirubin 12 months after starting UDCA therapy have an outcome free of liverrelated death, transplantation, progression to cirrhosis or liver failure. 51 A combined analysis of three randomized-controlled trials, including 548 PBC patients, showed improved survival without liver transplantation in patients with moderate to severe disease treated with UDCA at doses of 13-15 mg/kg/day for up to 4 years.…”
Section: Therapymentioning
confidence: 99%
“…In distinction to the autoimmune biliary diseases, autoimmune hepatitis (AIH) is a predominantly lymphoplasmacytic interface hepatitis, that is associated with elevated globulins, and frequent, usually non-specific, autoantibody associations. Unlike PBC and PSC that have a paucity of effective medical treatment, this autoimmune liver disease is highly steroid responsive [4]. …”
Section: Introductionmentioning
confidence: 99%